Malnutrition and frailty in community dwelling older adults living in a rural setting. Issue 1 (February 2016) - Boulos, Christa; Salameh, Pascale; Barberger-Gateau, Pascale
Summary: Background & aims: Malnutrition and frailty are frequent and serious conditions within the geriatric population. Both are of multifactorial origin and linked to adverse outcomes. The purpose of this study was to analyze the relationships between these two concepts in a representative sample of rural elderly Lebanese with a high prevalence of malnutrition. Methods: A cross-sectional study including a representative sample of 1200 elderly Lebanese aged 65 and over living in the community. The following measurements were recorded: information on socio-demographic status, comorbidities, Activities of Daily Living (ADL), screening for depression (5 item Geriatric Depression Scale [GDS]) and cognitive status (Mini-Mental-State [MMS]). Frailty was assessed through the Study of Osteoporotic Fractures (SOF) index whereas nutritional status was measured through the Mini Nutritional Assessment (MNA). Stepwise backwards multinomial logistic regression was used to analyze the association between nutritional status and frailty, independent of these covariates. Results: Frailty or prefrailty were present in respectively 36.4% and 30.4% of the participants. The proportion of individuals suffering from poor nutritional status increased with growing level of frailty (p < 0.001). Fourteen out of the 18 MNA items were associated with frailty in age-adjusted analyses. In the final multinominal logistic regression, both malnutrition and risk of malnutrition were related to a significantly increased risk of frailty, respectively (OR: 3.72, 95% IC: 1.40–9.94/OR: 3.66, 95% IC: 2.32–5.76), whereas the relation between poor nutritional status and prefrailty was not significant, independently of reporting less than three comorbidities, being ADL independent, depressive symptoms, illiteracy, and low cognitive status. Conclusion: Frailty and malnutrition are two closely related but distinct concepts that share common determinants in this elderly population.